Flux and solder paste
Patent Information
- Application Number
- JP2020119151
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-07-10
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2040-07-10
AI Technical Summary
【0019】 本発明によれば、作業性よく、ソルダペーストの断続印刷性を向上させることが可能なフラックス、及び、該フラックスを含むソルダペーストを提供することができる。
Smart Images

Figure 0007641610000001 
Figure 0007641610000002 
Figure 0007641610000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a flux used in soldering and a solder paste containing the flux. [Background technology]
[0002] A solder paste made of a mixture of a solder alloy and flux is used in mounting technology for mounting electronic components such as chip components and package substrates on electronic circuit boards such as printed wiring boards. Specifically, the solder paste is screen-printed onto the pads on the surface of the electronic circuit board using a metal mask, and then the electronic components are mounted and heated (reflowed) to bond the electronic components onto the electronic circuit board.
[0003] In recent years, electronic components have become smaller as electronic devices become smaller and their performance improves. As a flux for improving the printability of such fine electronic components, for example, Patent Document 1 discloses a flux containing a solvent containing a higher alcohol that has a carbon number of 12 to 22 and is liquid at room temperature. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2020-49539 A Summary of the Invention [Problem to be solved by the invention]
[0005] From the viewpoint of workability, screen printing may be performed intermittently at regular intervals. However, after screen printing, a small amount of solder paste adheres to the openings of the metal mask. The adhered solder paste dries over time and adheres to the openings of the metal mask, and may even cause clogging, which may result in a reduced amount of solder paste to be filled when the next screen printing is performed, making printing defects more likely to occur. Although it is possible to wash off the solder paste that has adhered to the openings of the metal mask, this is not preferred as it is less workable.
[0006] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a flux that is easy to work with and can improve the intermittent printability of a solder paste, and a solder paste containing the flux. [Means for solving the problem]
[0007] The flux according to the present invention is used for soldering and contains a solvent including butyl triglycol.
[0008] With this configuration, the flux does not dry out easily even when left for a certain period of time, and since it suppresses an increase in adhesion, the solder paste is less likely to stick to the openings of the metal mask after screen printing, and furthermore, clogging is less likely to occur. As a result, the flux can improve the intermittent printability of the solder paste without the need for work such as washing off the solder paste.
[0009] In the flux according to the present invention, the content of the butyl triglycol may be 30.0% by mass or more and 55.0% by mass or less with respect to the entire flux.
[0010] With this configuration, the solder paste is less likely to stick to the openings of the metal mask after screen printing, and furthermore, clogging is less likely to occur. As a result, the flux can further improve the intermittent printability of the solder paste.
[0011] The solder paste according to the present invention contains the above-mentioned flux and a solder alloy powder.
[0012] The flux does not dry easily even if left for a certain period of time, and also suppresses an increase in adhesion, so that the solder paste is less likely to stick to the openings of the metal mask after screen printing, and is less likely to cause clogging. As a result, the solder paste can improve intermittent printability without the need for operations such as washing it off.
[0013] In the solder paste according to the present invention, the particle size of the solder alloy powder may be 5 μm or more and 40 μm or less.
[0014] Since the particle size of the solder alloy powder is within the above-mentioned range, the solder paste can have good workability and improved intermittent printability in a wide range of applications, from solder pastes for general use to solder pastes for fine printing.
[0015] In the solder paste according to the present invention, the alloy of the solder alloy powder may be a Sn / Ag / Cu alloy.
[0016] The solder paste has good workability and can improve intermittent printability even for the widely and commonly used Sn / Ag / Cu alloy.
[0017] In the solder paste according to the present invention, the Sn / Ag / Cu alloy may further contain at least one element selected from the group consisting of In, Bi, Sb and Ni.
[0018] Even if these metal elements are added to the solder paste for the purpose of improving the thermal durability of the solder alloy, the solder paste can have good workability and improved intermittent printability. Effect of the Invention
[0019] According to the present invention, it is possible to provide a flux that is easy to work with and that can improve the intermittent printability of a solder paste, and a solder paste that contains the flux. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] Hereinafter, the flux and solder paste according to the embodiment of the present invention will be described.
[0021] <Flux>
[0022] (solvent) The flux according to the present embodiment contains butyl triglycol as a solvent. The content of butyl triglycol is preferably 30.0 mass% or more, more preferably 40.0 mass% or more, based on the total flux. The content of butyl triglycol is preferably 55.0 mass% or less, more preferably 47.0 mass% or less, based on the total flux.
[0023] The flux according to the present embodiment may contain other solvents besides butyl triglycol. The other solvents are not particularly limited, and may be, for example, known solvents such as glycol ethers such as diethylene glycol monohexyl ether (hexyl diglycol), diethylene glycol dibutyl ether (dibutyl diglycol), diethylene glycol mono 2-ethylhexyl ether (2 ethylhexyl diglycol), and diethylene glycol monobutyl ether (butyl diglycol); aliphatic compounds such as n-hexane, isohexane, and n-heptane; esters such as isopropyl acetate, methyl propionate, and ethyl propionate; ketones such as methyl ethyl ketone, methyl-n-propyl ketone, and diethyl ketone; and alcohols such as ethanol, n-propanol, isopropanol, and isobutanol. The solvents may be used alone or in combination of two or more.
[0024] The content of the other solvent is preferably 5.0% by mass or more, more preferably 10.0% by mass or more, based on the total flux. The content of the other solvent is preferably 20.0% by mass or less, more preferably 15.0% by mass or less, based on the total flux. When two or more kinds of other solvents are contained, the above content is the total content of the other solvents.
[0025] (resin) The flux according to the present embodiment may contain a resin. Examples of the resin include rosin-based resin and synthetic resin. The rosin-based resin is not particularly limited, and one or more types of rosin-based resin selected from rosin and rosin derivatives (e.g., hydrogenated rosin, polymerized rosin, disproportionated rosin, acrylic acid modified rosin, etc.) can be used. The synthetic resin is not particularly limited, and known synthetic resins can be used. The resins may be used alone or in combination of two or more types.
[0026] The resin content is preferably 30.0% by mass or more, more preferably 40.0% by mass or more, based on the total weight of the flux. The resin content is preferably 70.0% by mass or less, more preferably 50.0% by mass or less, based on the total weight of the flux. When two or more types of resin are included, the above content is the total content of the resins.
[0027] (thixotropic agent) The flux according to the present embodiment may further contain a thixotropic agent in order to further enhance the thixotropic properties of the flux. Examples of the thixotropic agent include castor hardened oil, fatty acid amide, fatty acid bisamide, polyamide compound, kaolin, colloidal silica, organic bentonite, and glass frit. Among these, the thixotropic agent is preferably a fatty acid bisamide or a polyamide compound in terms of heat resistance. Examples of the fatty acid amide include stearic acid amide, lauric acid amide, palmitic acid amide, oleic acid amide, erucic acid amide, behenic acid amide, myristic acid amide, and N-hydroxyethyl-12-stearyl amide. Examples of fatty acid bisamides include methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, ethylene bisstearic acid amide, ethylene bishydroxystearic acid amide, ethylene bisbehenic acid amide, hexamethylene bisstearic acid amide, hexamethylene bisbehenic acid amide, hexamethylene bis-12-hydroxystearic acid amide, N,N'-distearyl adipic acid amide, and N,N'-xylylene bis-12-hydroxystearyl amide. Examples of polyamide compounds include aliphatic polyamide compounds such as VA-79, AMX-6096A, WH-215, and WH-255 (all manufactured by Kyoeisha Chemical Co., Ltd.), SP-10 and SP-500 (all manufactured by Toray Industries, Inc.), Grilamid L20G and Grilamid TR55 (all manufactured by MSC Japan Co., Ltd.), and aromatic polyamide compounds (semi-aromatic polyamide compounds or fully aromatic polyamide compounds) containing cyclic compounds such as benzene rings and naphthalene rings in the main chain, such as JH-180 (manufactured by Ito Oil Mills, Inc.). The thixotropic agents may be used alone or in combination of two or more.
[0028] The content of the thixotropic agent is preferably 1.0 mass% or more, more preferably 3.0 mass% or more, based on the total flux. The content of the thixotropic agent is preferably 7.0 mass% or less, more preferably 5.0 mass% or less, based on the total flux. When two or more types of thixotropic agents are included, the above content is the total content of the thixotropic agents.
[0029] (Activator) The flux according to the present embodiment may contain an activator. The activator is not particularly limited, and examples thereof include organic acid activators, amine compounds, amino acid compounds, and halogen-based activators such as amine halogen salts and halogen compounds. The activators may be used alone or in combination of two or more.
[0030] The organic acid surfactant is not particularly limited, and examples thereof include monocarboxylic acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, enanthic acid, capric acid, lauric acid, myristic acid, pentadecylic acid, palmitic acid, margaric acid, stearic acid, tuberculostearic acid, arachidic acid, behenic acid, lignoceric acid, and glycolic acid; dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, methylsuccinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, fumaric acid, maleic acid, tartaric acid, and diglycolic acid; and other organic acids such as dimer acid, levulinic acid, lactic acid, acrylic acid, benzoic acid, salicylic acid, anisic acid, citric acid, picolinic acid, tris(2-carboxyethyl)isocyanuric acid, and tris(2-carboxypropyl)isocyanuric acid.
[0031] The amine compound is not particularly limited, and examples thereof include tetraacetylethylenediamine (N,N,N',N'-tetraacetylethylenediamine), N-acetylimidazole, N-acetylphthalimide, acetamidobenzoic acid (3-acetamidobenzoic acid, 4-acetamidobenzoic acid), N-acetylanthranilic acid, acetamidonitrobenzoic acid (2-acetamido-6-nitrobenzoic acid, 3-acetamido-4-nitrobenzoic acid, 3-acetamido-2-nitrobenzoic acid, 5-acetamido-2-nitrobenzoic acid), and the like.
[0032] The amino acid compound is not particularly limited, and examples thereof include N-acetylphenylalanine (N-acetyl-L-phenylalanine, N-acetyl-DL-phenylalanine, N-acetyl-D-phenylalanine), N-acetylglutamic acid (N-acetyl-L-glutamic acid), N-acetylglycine, N-acetylleucine (N-acetyl-L-leucine, N-acetyl-DL-leucine, N-acetyl-D-leucine), and N-acetylphenylglycine (N-acetyl-N-phenylglycine, N-acetyl-L-phenylglycine, N-acetyl-DL-phenylglycine).
[0033] Examples of the amines in the amine halogen salts include diethylamine, dibutylamine, tributylamine, diphenylguanidine, and cyclohexylamine. Examples of the halogens in the amine halogen salts include fluorine, chlorine, bromine, and iodine. Examples of the halogen compounds include tris(2,3-dibromopropyl)isocyanuric acid, 2,3-dibromo-2-butene-1,4-diol, 2-bromo-3-iodo-2-butene-1,4-diol, and TBA-bis(2,3-dibromopropyl ether).
[0034] The content of the activator is preferably 0.5% by mass or more, more preferably 3.0% by mass or more, based on the total flux. The content of the activator is preferably 20.0% by mass or less, more preferably 10.0% by mass or less, based on the total flux. When a halogen-based activator is included as the activator, the content is preferably 0.1% by mass or less, from the viewpoint of environmental load. When two or more types of activators are included, the above content is the total content of the activators.
[0035] The flux according to the present embodiment may contain at least one of the following other additives: a stabilizer, a surfactant, a defoamer, and a corrosion inhibitor. The total content of the other additives is not particularly limited, and may be, for example, 5.0 mass% or less with respect to the entire flux.
[0036] The flux according to the present embodiment contains a solvent containing butyl triglycol, which makes it difficult to dry out even when left for a certain period of time, and also suppresses an increase in adhesion, so that the solder paste is less likely to stick to the openings of the metal mask after screen printing, and furthermore, is less likely to cause clogging. As a result, the flux can improve the intermittent printability of the solder paste without the need for operations such as washing off the solder paste.
[0037] In the flux according to the present embodiment, the content of the butyl triglycol is 30.0% by mass or more and 55.0% by mass or less based on the total mass of the flux, so that the solder paste is less likely to stick to the openings of the metal mask after screen printing, and furthermore, clogging is less likely to occur, and as a result, the flux can further improve the intermittent printability of the solder paste.
[0038] <Solder paste> The solder paste according to the present embodiment contains the above-mentioned flux and solder alloy powder. The solder paste is obtained by mixing the flux and the solder alloy powder. The content of the flux is preferably 5 to 20 mass % based on the total amount of the solder paste. The content of the solder alloy powder is preferably 80 to 95 mass % based on the total amount of the solder paste.
[0039] The particle size of the solder alloy powder is preferably 5 μm or more and 40 μm or less, and more preferably 15 μm or more and 28 μm or less.
[0040] The alloy of the solder alloy powder includes lead-free solder alloys and eutectic solder alloys containing lead, but from the viewpoint of reducing environmental load, the lead-free solder alloy is preferable. The lead-free solder alloy includes, for example, alloys containing tin, silver, copper, indium, zinc, bismuth, antimony, etc. More specifically, alloys such as Sn / Ag, Sn / Ag / Cu, Sn / Cu, Sn / Ag / Bi, Sn / Bi, Sn / Ag / Cu / Bi, Sn / Sb, Sn / Zn / Bi, Sn / Zn, Sn / Zn / Al, Sn / Ag / Bi / In, Sn / Ag / Cu / Bi / In / Sb, and In / Ag are examples. Among these, the alloy of the solder alloy powder is preferably an Sn / Ag / Cu alloy. In addition, it is more preferable that the Sn / Ag / Cu alloy further contains at least one selected from In, Bi, Sb, and Ni. The alloy also contains unavoidable impurities, which are components that are inevitably mixed in during the manufacturing process and are acceptable to the extent that they do not affect the effects of the present invention.
[0041] The solder paste according to the present embodiment contains the above-mentioned flux and a solder alloy powder. The flux does not dry easily even when left for a certain period of time, and also suppresses an increase in adhesion, so that the solder paste is less likely to stick to the openings of the metal mask after screen printing, and is less likely to cause clogging. As a result, the solder paste can improve intermittent printability without the need for washing off or other operations.
[0042] The solder paste of this embodiment has a particle diameter of the solder alloy powder of 5 μm or more and 40 μm or less, and therefore can provide good workability and improved intermittent printability in a wide range of applications, from solder pastes for general-purpose use to solder pastes for fine printing.
[0043] In the solder paste according to the present embodiment, the alloy of the solder alloy powder may be a Sn / Ag / Cu alloy. The solder paste has good workability and can improve intermittent printability even for the widely and commonly used Sn / Ag / Cu alloy.
[0044] In the solder paste according to the present embodiment, the Sn / Ag / Cu alloy may further contain at least one selected from the group consisting of In, Bi, Sb, and Ni. Even if these metal elements are added for the purpose of improving the thermal durability of the solder alloy, the solder paste can have good workability and improve intermittent printability. EXAMPLES
[0045] Examples of the present invention will be described below, but the present invention is not limited to the following examples.
[0046] <Preparation of solder paste> The resin, solvent, thixotropic agent, activator, and antioxidant in the amounts shown in Tables 1 to 3 were placed in a heating container and heated to 180°C to obtain a varnish component. The varnish component and other components were then mixed at room temperature to obtain a uniformly dispersed flux. The amounts of each component shown in Table 1 are equal to the contents of each component contained in the flux. Next, 11.8 mass% of each flux and 88.2 mass% of the solder alloy powder shown in Tables 1 to 3 were mixed to obtain a solder paste for each Example and Comparative Example.
[0047] [Table 1]
[0048] [Table 2]
[0049] [Table 3]
[0050] Details of each raw material contained in the flux shown in Tables 1 to 3 are shown in Table 4. Details of the solder alloys shown in Tables 1 to 3 are shown in Table 5.
[0051] [Table 4]
[0052] [Table 5]
[0053] <Evaluation of intermittent printing> 300 g of the solder paste of each Example and Comparative Example was placed on a metal mask set on a printing machine (YVP-Xg, manufactured by YAMAHA Motor Co., Ltd.), and rolling was performed four times to make the solder paste blend into the metal mask. Then, the back of the metal mask was dry-cleaned, and the first printing was performed under the printing conditions below. After that, the mask was left to stand for 60 or 120 minutes in an environment of temperature: 24 to 26°C and humidity: 50 to 60% RH, and the back of the metal mask was dry-cleaned, and the second printing was performed under the printing conditions below. The first printing was performed on two sheets, and the transfer rate was evaluated for the first sheet.
[0054] (Printing conditions) Printing squeegee: Metal squeegee Squeegee angle: 60° Metal mask thickness: 120μm Printing speed: 40mm / sec Pad shape: O-shaped (0.25mmφ) or □-shaped (0.25mm×0.25mm) Number of pads: 50 Pad material: OSP treated copper
[0055] (Evaluation of transcription rate) The solder transfer rate was calculated by detecting the solder on the copper pads of each printed board using a KOHYOUNG aSPIer and calculating the volume percentage. The average volume percentage for 50 pads is shown in Tables 1 to 3.
[0056] In addition, if even one pad was judged to have a volume percentage of less than 10%, it was determined that there was a removal defect. The results are shown in Tables 1 to 3.
[0057] Based on the average volume % and the results of removal failure, a rating of A to E was given according to the criteria in Table 6. The results are shown in Tables 1 to 3. Solder pastes rated A to C were deemed acceptable, and solder pastes rated D and E were deemed unacceptable.
[0058] [Table 6]
[0059] As can be seen from the results in Table 1, the solder pastes of the examples which met all of the requirements of the present invention had an average volume percentage of 70% or more after 60 minutes of printing and no printout defects, demonstrating excellent intermittent printability.
[0060] Furthermore, as can be seen from the results in Table 3, the solder paste of Example 15, which satisfies all of the requirements of the present invention, exhibits excellent intermittent printability, as the average volume percentage after 120 minutes of printing is 70% or more and there are no printout defects.
[0061] On the other hand, as can be seen from the results in Tables 2 and 3, the solder pastes of each comparative example that did not contain butyl triglycol had an average volume percentage of less than 70% after 60 minutes and 120 minutes of printing for at least one of the pad shapes, namely, circle and square, and thus had poor intermittent printability.
Claims
1. A flux used in soldering, A solvent containing butyl triglycol (excluding those containing a diglycerol EO adduct, a diglycerol PO adduct, or a glycerol EO / PO adduct) and a resin, The content of the butyl triglycol is 30.0 mass% or more and 55.0 mass% or less with respect to the entire flux, A flux, the content of the resin being 30.0 mass % or more and 70.0 mass % or less with respect to the entire flux.
2. The soldering flux contains a solvent including butyl triglycol, and a solder alloy powder. The alloy of the solder alloy powder is a Sn / Ag / Cu alloy; The solder paste has a content of the butyl triglycol of 30.0 mass % or more and 55.0 mass % or less based on the total mass of the flux.
3. 3. The solder paste according to claim 2, wherein the particle size of the solder alloy powder is 5 μm or more and 40 μm or less.
4. The solder paste according to claim 2 or 3, wherein the Sn / Ag / Cu alloy further contains at least one selected from the group consisting of In, Bi, Sb and Ni.
Citation Information
Patent Citations
Flux composition for soldering and electronic circuit board using the same
JP2015208770A
Solder composition and electronic substrate
JP2017064760A
flux
JP2018196900A
Solder paste
JP2019181561A
Solder alloy, solder powder, solder paste, and solder joint with use thereof
JP2020011280A